Experimental Mathematics. Volume 18, Number 1, 2009 - A K Peters (A K Peters, 2009)
A Generalization of Siegel's Theorem and Hall's Conjecture Full TextPDF (211.7 KB) Authors Graham Everest and Valéry Mahé 1-9 No access to content Motivic Proof of a Character Formula for SL(2) Full TextPDF (518.7 KB) Authors Clifton Cunningham and Julia Gordon 11-44 No access to content Discrete Morse Functions from Fourier Transforms Full TextPDF (734.9 KB) Author Alexander Engström 45-53 No access to content Frequencies of Successive Tuples of Frobenius Classes Full TextPDF (215.4 KB) Authors Avner Ash, Brandon Bate and Robert Gross 55-63 No access to content Jacobians of Genus-2 Curves with a Rational Point of Order 11 Full TextPDF (211.3 KB) Authors Nicolas Bernard, Franck Leprévost and Michael Pohst 65-70 No access to content Algorithms for Projectivity and Extremal Classes of a Smooth Toric Variety Full TextPDF (344.6 KB) Author Anna Scaramuzza 71-84 No access to content Low-Degree Cohomology of Integral Specht Modules Full TextPDF (265.8 KB) Author Christian Weber 85-95 No access to content Some Conjectures and Open Problems on Partition Hook Lengths Full TextPDF (219.2 KB) Author Guo-Niu Han 97-106 No access to content Resolution of the Quinn–Rand–Strogatz Constant of Nonlinear Physics Full TextPDF (254.9 KB) Authors D. H. Bailey, J. M. Borwein and R. E. Crandall 107-116 No access to content Convergence Properties of Donaldson's T -Iterations on the Riemann Sphere Full TextPDF (445.8 KB) Author Morgan Sherman